Wujud Nasionalisme Tokoh Modernis Islam: Kontribusi K.H. Mas Mansur dalam Mengantarkan Indonesia Merdeka - Miftahuddin, Miftahuddin; Widiyanta, Danar; Rafsanjani, Adnan (Jurnal Sejarah Citra Lekha, 2024)
This study aims to reaffirm the role of K.H. Mas Mansur in the context of Indonesia's struggle for independence from colonial rule. The research employs historical research procedures, including heuristics (source gathering), verification (criticism of the collected sources), interpretation (analysis of historical facts), and historiography (writing of history). The results of this study indicate that K.H. Mas Mansur's contributions to Indonesia's independence were realized both in the fields of social-religious movements to advance Islam and in politics. K.H. Mas Mansur viewed his involvement in social-religious affairs as important, seeing it as a means of empowering society in relation to understanding Islam as a way of life. Similarly, K.H. Mas Mansur believed that achieving an independent Indonesia required the development of political awareness, as resistance against the colonizers would not succeed without this consciousness. The development of the Indonesian Islamic Party (PII), for example, cannot be separated from Mas Mansur's role as a high-ranking leader of Muhammadiyah. In this context, it is clear that, alongside his active participation in the social-religious organization Muhammadiyah and his leadership within it, Mas Mansur was also deeply involved in politics.